How to Identify a Tree - Michael G. Andreu; Erin M. Givens; Melissa H. Friedman (EDIS, 2010)
FOR234, a 22-page illustrated fact sheet by Michael G. Andreu, Erin M. Givens, and Melissa H. Friedman, guides readers through the process of identifying a tree. Includes references and a tree identification sheet. Published by the UF School of Forest Resources and Conservation, April 2010.